1985
DOI: 10.1002/clc.4960080106
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Q wave in acute myocardial infarction

Abstract: Summary: Acute myocardial infarction may be associated with the development of Q waves on the electrocardiogram (ECG), or with changes limited to the ST segment or T wave. The ECG changes do not accurately differentiate transmural from nontransmural infarction. However, the presence or absence of a Q wave does correlate with some aspects of the clinical course of patients after myocardial infarction, and is therefore of prognostic value. Q-wave infarctions are more likely to be complicated by congestive heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, a Q-wave's existence or absence corresponds with several features of a patient's post-MI clinical history and hence has predictive significance. Congestive heart failure is more likely to worsen Q-wave infarctions while they are being treated in the hospital [ 20 ]. Congestive heart failure was more likely to occur later in participants who had their first Q-wave infarction, although coronary insufficiency was more common in participants who had their first non-Q-wave infarction [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…On the other hand, a Q-wave's existence or absence corresponds with several features of a patient's post-MI clinical history and hence has predictive significance. Congestive heart failure is more likely to worsen Q-wave infarctions while they are being treated in the hospital [ 20 ]. Congestive heart failure was more likely to occur later in participants who had their first Q-wave infarction, although coronary insufficiency was more common in participants who had their first non-Q-wave infarction [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…It has been indicated that Q-wave infarction is associated with higher levels of certain enzymes including serum glutamicoxaloacetic transaminase (SGOT), lactate dehydrogenase (LDH), and creatinine phosphokinase. These high enzyme levels are caused by the presence of considerable myocardial necrosis presence [4][5][6].…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Finally, table II summarizes the mean peak CK data for all 544 patients with isoenzyme-confirmed acute non-Q wave MI. In spite of the fact that 48% of the study cohort had 'combination location' non-Q wave infarcts, their peak Other investigators have lobbied passionately for abandonment of the terms 'transmural' and 'nontransmural' in favor of Q wave and non-Q wave MI [2, 3,[27][28][29], Still others have advocated the adoption of a terminology which comprises 'Q wave MF, 'S-T MF and 'T wave MF [3,30,31], Indeed, Spodick [3] has elo quently emphasized the nonspecificity of ECG criteria for differentiating transmural and nontransmural le sions, pointing out that despite the clinical, physiologic and prognostic differences between the two infarct sub-CK values were not significantly different from the sub groups whose non-Q wave MI was localized to a single lead group.Thus, the early ECG findings in non-Q wave MI were most frequently 'global' (i.e. multiple lead group loca tions), were less commonly isolated to a single ECG loca tion and were nonlocalizable in almost 20% of patients.…”
mentioning
confidence: 99%